Building ubiquitination machineries: E3 ligase multi-subunit assembly and substrate targeting by PROTACs and molecular glues. (April 2021) - Ramachandran, Sarath; Ciulli, Alessio
Graphical abstract: Highlights: E3 ligase machineries confer specificity to protein ubiquitination. Multi-subunit assembly and substrate recognition impact E3 ligase activity. Molecular glues and PROTACs recruit proteins to E3 ligases for targeted degradation. E3: PROTAC/glue: target ternary complex structures can accelerate degrader design. Abstract : E3 ubiquitin ligase machineries are emerging as attractive therapeutic targets because they confer specificity to substrate ubiquitination and can be hijacked for targeted protein degradation. In this review, we bring to focus our current structural understanding of E3 ligase complexes, in particular the multi-subunit cullin RING ligases, and modulation thereof by small-molecule glues and PROTAC degraders. We highlight recent advances in elucidating the modular assembly of E3 ligase machineries, their diverse substrate and degron recognition mechanisms, and how these structural features impact on ligase function. We then outline the emergence of structures of E3 ligases bound to neo -substrates and degrader molecules, and highlight the importance of studying such ternary complexes for structure-based degrader design.